PENGARUH DIGITAL MARKETING, VARIASI PRODUK, DAN STORE ATMOSPHERE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PESSO CAFE SANUR - Pande Diva Darma Diputra; I Nengah Suardhika; Ni Putu Cempaka Dharmadewi Atmaja (Jurnal Bakti Saraswati (JBS), 2025)
Coffee consumption has become part of the modern lifestyle, especially among the younger generation. Coffee shops are developing as comfortable places to relax, enjoy coffee and take photos, along with increasing demand and urbanization in Indonesia, especially in Bali. This creates promising business opportunities in the coffee shop industry. This research aims to determine and analyze the influence digital marketing, product variations, and store atmosphere against the purchase decision on Pesso Cafe Sanur. The number of samples used in this research was 96 respondents who were Pesso customers Cafe Sanur, by taking samples using techniques purposive sampling. Data was taken using a Likert scale questionnaire and processed using IBM SPSS Statistics 26.0 for Windows. The research results prove that digital marketing positive and significant effect on purchasing decisions, product variety has a positive and significant effect on purchasing decisions, and store atmosphere positive and significant effect on purchasing decisions.